Genetic and Phenotypic Screening of Mannose-Binding Lectin in Relation to Risk of Recurrent Vulvovaginal Infections in Women of North India: A Prospective Cohort Study - Kalia, Namarta; Singh, Jatinder; Sharma, Sujata; Arora, Hardesh; Kaur, Manpreet (Frontiers in Microbiology, 2017)
Recurrent Vulvovaginal Infections (RVVI) is common problem associated with women of reproductive age. The function and deleterious effect of Mannose Binding Lectin 2 (MBL2) common polymorphisms are reported to be associated with various diseases. However, the role of MBL2 promoter gene polymorphisms and their combined effect with structural variant along with Serum Mannose Binding Lectin (sMBL) levels in RVVI has not been investigated. The study included 258 RVVI cases and 203 age matched healthy controls. These were investigated for the distribution of MBL2 codon 54 and promoter polymorphisms by Amplification Refractory Mutation System-Polymerase Chain Reaction (ARMS-PCR). sMBL levels were quantified by Enzyme Linked Immnosorbent Assay (ELISA). The frequency of X allele and its genotypes was significantly high in cases than controls conferring risk towards RVVI and its types (p<0.05). The HXPA (OR; 2.0), LXQB (OR; 1.43) haplotypes were associated with susceptibility to RVVI cases while haplotype LYQB significantly protected against RVVI (OR; 0.58), Bacterial Vaginosis (BV) (OR; 0.27) and Mixed Infections (MI) cases (OR; 0.62) with high frequency observed in controls (p<0.05). Mean sMBL levels were significantly low in RVVI, BV, Vulvovaginal Candidiasis (VVC) and MI cases compared to controls (p<0.05). VVC patient showed significantly low sMBL levels than RVVI and MI cases (p<0.05). The mean sMBL levels segregated based on MBL2 genotypes and haplotypes showed significant difference in different cases groups with controls. The findings of the present study suggested that MBL2 Y/X polymorphism and low sMBL levels were associated with susceptibility to RVVI either it is BV, VVC or MI. Thus MBL deficiency in women with RVVI may contribute to decreased efficiency in clearing of pathogens. Hence, specific measures like administration of purified or recombinant MBL might decrease the incidence of vaginal infections recurrences and more-effective treatment.